2001
DOI: 10.1128/jvi.75.14.6498-6507.2001
|View full text |Cite
|
Sign up to set email alerts
|

Transactivation of Murine Cyclin A by Polyomavirus Large and Small T Antigens

Abstract: Polyomavirus large and small T antigens cooperate in the induction of S phase in serum-deprived Swiss 3T3 cells. While the large T antigen is able to induce S phase-specific enzymes, we have recently shown that both T antigens contribute to the production of the cyclins E and A and that the small T antigen is essential for the induction of cyclin A-dependent cdk2 activity (S. Schüchner and E. Wintersberger, J. Virol. 73:9266-9273, 1999). Here we present our attempts to elucidate the mechanisms by which the lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 50 publications
3
11
0
Order By: Relevance
“…Thus, in the presence of LT and activated Ras signaling, the NH 2 -terminal domain of ST appears to be sufficient to drive cells into S phase. Consistent with this hypothesis, mutations in the DnaJ domain of polyoma ST has been shown to strongly inhibit activation of the cyclin A promoter (50).…”
Section: Discussionsupporting
confidence: 58%
“…Thus, in the presence of LT and activated Ras signaling, the NH 2 -terminal domain of ST appears to be sufficient to drive cells into S phase. Consistent with this hypothesis, mutations in the DnaJ domain of polyoma ST has been shown to strongly inhibit activation of the cyclin A promoter (50).…”
Section: Discussionsupporting
confidence: 58%
“…For growth arrest, asynchronously growing cells were seeded at 5 ϫ 10 5 cells per 100-mm-diameter petri dish; the next day, the serum concentration was reduced to 0.2% for 72 h. The cells were then either reinduced by addition of fresh medium containing 20% FCS or treated with dexamethasone at a concentration of 10 Ϫ6 mol/liter. Cell lines expressing the wild-type Py LT antigen (LTwt) and the E145D, P43A, and C452S mutant forms were described previously (31). Cell lines conditionally expressing LT antigens with other point mutations in the C-terminal region (Y442S and P670S) were produced by Polybrene-assisted transfections as described previously (24,31).…”
Section: Plasmidsmentioning
confidence: 99%
“…Mutations in either one of these sites abolish the transactivation of S phase-specific genes by LT antigen. In our previous work on Py LT antigen-mediated transactivation of the genes coding for thymidine kinase (25) and cyclin A (31), we observed that, in addition to the N terminus, regions within the C-terminal part of the LT protein play an important role (31). A mutation of the zinc finger present within this domain (C452S) interferes with transactivation.…”
mentioning
confidence: 99%
“…SV40 sT regulates cell cycle progression at least in part through induction of cyclins D1 and A (49,56). Polyomavirus sT has been shown to promote cell cycle progression (34) and to synergize with large T for S-phase induction in Swiss 3T3 mouse fibroblasts (47,48). sT/PP2A may also affect rates and efficiency of encapsidation through phosphorylation of VP1 (18).…”
Section: Discussionmentioning
confidence: 99%